2022
DOI: 10.1002/vzj2.20202
|View full text |Cite
|
Sign up to set email alerts
|

Same soil, different climate: Crop model intercomparison on translocated lysimeters

Abstract: Crop model intercomparison studies have mostly focused on the assessment of predictive capabilities for crop development using weather and basic soil data from the same location. Still challenging is the model performance when considering complex interrelations between soil and crop dynamics under a changing climate. The objective of this study was to test the agronomic crop and environmental flux‐related performance of a set of crop models. The aim was to predict weighing lysimeter‐based crop (i.e., agronomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 118 publications
(181 reference statements)
0
2
0
Order By: Relevance
“…In our analysis, we focus solely on the relative changes in future mean yields and have not conducted historical simulations for model validation. While previous studies have demonstrated the reliability of PCSE (WOFOST) in crop yield simulations (Asseng et al., 2019; Gaso et al., 2021; Groh et al., 2022; Müller et al., 2021), its validation in NEC has not been performed to date. Furthermore, the potential impact of new pest and disease distributions resulting from climate change is qualitatively understood but has not been incorporated into any models, leading to an overly optimistic assessment (Tubiello et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our analysis, we focus solely on the relative changes in future mean yields and have not conducted historical simulations for model validation. While previous studies have demonstrated the reliability of PCSE (WOFOST) in crop yield simulations (Asseng et al., 2019; Gaso et al., 2021; Groh et al., 2022; Müller et al., 2021), its validation in NEC has not been performed to date. Furthermore, the potential impact of new pest and disease distributions resulting from climate change is qualitatively understood but has not been incorporated into any models, leading to an overly optimistic assessment (Tubiello et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While the mean annual air temperature depicted in Figure 3f does not exceed this threshold, under SSP585, 66.40% of the days, particularly during the growing season (April-September), recorded temperatures above 22°C. The multi-model ensemble mean/median consistently outperforms individual models under high temperature conditions (Asseng et al, 2019;Groh et al, 2022). Therefore, the development of intercomparison projects for crop modeling should be considered as an effective approach to mitigate uncertainties during periods of high temperature in future studies.…”
Section: Limitations Of Our Studymentioning
confidence: 99%
“…SWC is measured within each lysimeter at a depth of 0.1 m below the surface with time domain reflectometry probes (CS610, Campbell Scientific, North Logan, UT, USA) at a resolution of 0.1 % SWC, according to the manufacturer. More details on the technical specifications of lysimeter facilities within SOILCan are given in Pütz et al (2016), on excavation methods in Pütz and Groh (2023), and on the Selhausen facility in Groh et al (2022).…”
Section: Eddy Covariance and Lysimeter Measurementsmentioning
confidence: 99%
“…Peters et al, 2017). Lysimeter data was used to determine the impact of changing climate and land use management on terrestrial hydrology and nutrient cycles for grasslands (Fu et al, 2017), and arable land (Groh et al, 2022). The temporally highly resolved measurements of hydraulic state variables and water fluxes have allowed to (a) advance the understanding of soil hydrology and inform new models (Hannes et al, 2016;Herbrich & Gerke, 2017) The TERENO design also extends the experimental catchment concept to stream reaches for improved understanding of aquatic ecosystem functions.…”
Section: Enabling Large-scale Experimentationmentioning
confidence: 99%
“…TERENO‐derived algorithms assure data quality and compute the water fluxes across the upper and lower boundaries of the lysimeters (e.g., Hannes et al., 2015; A. Peters et al., 2017). Lysimeter data was used to determine the impact of changing climate and land use management on terrestrial hydrology and nutrient cycles for grasslands (Fu et al., 2017), and arable land (Groh et al., 2022). The temporally highly resolved measurements of hydraulic state variables and water fluxes have allowed to (a) advance the understanding of soil hydrology and inform new models (Hannes et al., 2016; Herbrich & Gerke, 2017), (b) evaluate energy balance closure of eddy‐covariance stations (Mauder et al., 2018), (c) test crop yield models (Kamali et al., 2022), (d) predict impacts of climate change water use efficiency and plant growths (Jarvis et al., 2022), and (e) validate large scale model simulations of the German Drought Monitor (Boeing et al., 2022) and remotely sensed products (Trigo et al., 2018).…”
Section: Tereno—a Network Of Four Integrated Environmental Observatoriesmentioning
confidence: 99%